Comparative Economics of Various Management Regimes of Chaur Fisheries in Koshi- Gandak River Basin of Bihar - Raushan Kumar; Kumar, Nalini Ranjan (Fishery Technology, 2023)
The state of Bihar has about 35,000 hectares of chaurs (floodplains) which have immense potential for development of culture-based fisheries. However, the resource is either unutilized or underutilized and hence its productivity level is low. The low yield is mainly due to poor management of the resources for fisheries development. In this study, an attempt was made to analyse the prevalent management regimes of chaur fisheries to suggest suitable institutional options for its better utilization. For the purpose, a sample survey was conducted in Koshi- Gandak river basin in Bihar. The data was collected from 180 land owners, 58 fishers, 26 members of cooperative societies and 8 officials of Directorate of Fisheries, Government of Bihar. Estimate of yield, income and employment generation clearly demonstrated better management of chaurs by an entrepreneur and informal group than unmanaged fisheries or those managed by fishers/farmers’ co-operatives. This is mainly due to better management of resource by the entrepreneur and the informal groups. Therefore, there is a need to encourage fishers to form their own groups or develop entrepreneurship in themselves for managing the fishery resource for its better utilization. However, as per ‘Bihar Jalkar Adhiniyam, 2006’, government water bodies must be leased out to only fishers’ co-operative of the respective blocks and hence there is a need to amend the act accordingly to facilitate the leasing of water bodies to informal groups of fishers or entrepreneurs.